Zakat And Taxes As Islamic Fiscal Instruments: A Solution To The Double Tasking Debate - Suherli, Ian Rakhamawan; Janwari, Yadi; al Hakim, Sofyan; Sulaeman, Sulaeman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study aims to explore the integration of zakat and taxes as fiscal instruments in the Islamic economic system, focusing on the challenges and opportunities faced in its implementation. The method used is a qualitative approach with a comparative analysis of various existing literature and practices. The results indicate that despite significant challenges, such as legal complexity, community resistance to change, and the risk of corruption, this integration has the potential to improve efficiency, transparency, and accountability in fund management. Furthermore, this integration can provide legal clarity for zakat and tax payers and update potentially outdated regulations. This study recommends the need for close collaboration between the government, religious institutions, academics, and the community to create an effective and widely accepted system. Thus, the integration of zakat and taxes is expected to support sustainable socio-economic development in the context of a modern state.